A revision of the genus Nyctimenius Gressitt, 1951 (Coleoptera: Cerambycidae: Lamiinae), with description of a new species - Huang, Guiqiang; Liu, Zhiping; Chen, Li (Zootaxa, 2014)
A taxonomic revision of the genus Nyctimenius Gressitt is presented. A new species, N. chiangi sp. nov., is described from China. Two new combinations, N. mamutensis (Hayashi, 1975) comb. nov. and N. sabahensis (Hayashi, 1975) comb. nov., are proposed. A new status, N. palawanicus (Aurivillius, 1922) stat. n., is proposed, and a lectotype is designated for N. palawanicus. The male terminalia and aedeagus of N. ochraceovittatus are described for the first time. Nyctimenius is redescribed, and a key to Nyctimenius species is presented.